Treatment results, side effects and prognostic factors affecting survival in patients with larynx cancer - Yücel, Birsen; Ay Eren, Ayfer; Erdiş, Eda; Akgül Babacan, Nalan; Elif Altuntaş, Emine (ENT Updates, 2013)
Objective: Our aim was to determine the treatment results, side effects and the prognostic factors affecting survival in patients with larynx cancer treated in our clinic. Methods: Data of a total of 90 patients with larynx carcinoma were included in the study. The patients’ performance scores were evaluated according to the Eastern Cooperative Oncology Group (ECOG) system. Results: Eighty-seven (97%) patients were male and three patients (3%) were female. The median age of the patients was 59 (37-86) years. Early-stage, locally advanced stage, and metastatic disease were detected in 43, 55, and 2% of the patients, respectively. Laryngeal cancers were observed in the glottic (53%), and supraglottic (47%) regions. Performance score (p=0.022), grade (p=0.033), lymph node metastasis (p=0.001), T stage (p=0.034) and disease stage (p=0.007) were significantly unfavourable in supraglottic cancers compared to glottic cancers. Recurrence was observed in 17% of the patients in a median 15 (range: 5-96) months. Distant metastasis was observed in 12% of the patients in a median 17 (range: 1-155) months. The factors affecting survival were the presence of comorbidities (p=0.032), performance status (p=0.022), hemoglobin level (p=0.003), T stage (p=0.006), disease stage (p=0.011), and weight loss (p=0.002). When RT- and CRT-associated side effects were compared, the incidence of adverse effects such as mucositis (p<0.001), nausea/vomiting (p<0.001), weight loss (p=0.005), neutropenia (p=0.001), and anemia (p=0.003) in patients under chemoradiotherapy was significantly higher than those associated with radiotherapy. Conclusion: Hemoglobin level, T stage, presence of comorbidity and weight loss were independent prognostic factors.